2x-3(-1)=13

Simple and best practice solution for 2x-3(-1)=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-3(-1)=13 equation:


Simplifying
2x + -3(-1) = 13

Multiply -3 * -1
2x + 3 = 13

Reorder the terms:
3 + 2x = 13

Solving
3 + 2x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 2x = 13 + -3

Combine like terms: 3 + -3 = 0
0 + 2x = 13 + -3
2x = 13 + -3

Combine like terms: 13 + -3 = 10
2x = 10

Divide each side by '2'.
x = 5

Simplifying
x = 5

See similar equations:

| tan(x-10)=1.2 | | -9(3b+1)+(28b-4)=0 | | k-29=0 | | 2s+30+3s+50=180 | | (9b-8)-2(4b+3)=-6 | | x+8=266 | | Y=(3x+4)(x+11) | | k^3+k^2+20k=0 | | 1.3q-5.8-0.4q=-0.1q-2.7 | | 5(13-3a)=-25 | | 6x+4x+4+8=7x+3+2x | | 4x+5+2x=31 | | -44=-8(-2x+4) | | 4x+2y-3z+a=14 | | -94=8r+3(6-8r) | | (2j+3)-4j-(j+3)= | | 2x-3y+z+5a=-9 | | 2x^2-3px-p=0 | | 3x+15=17+x | | 330=-6(1-7x) | | sinx=0.359 | | 2x(2y-11)=80 | | x+5y=3y-2 | | 2n-8(1+3n)=-96 | | -137=-4(1+8m)-5 | | -137=-4(1+8m) | | 17x-3=3x | | 4x+32=-48 | | 84=-4(3+8x) | | 170=-5(1-7n) | | -5(6+2r)-3r=-108 | | 3m=m+10 |

Equations solver categories